Producción de Carbón Activado a partir de la Testa de la Almendra de Cacao - Rodríguez Estacio, John Smith (2022)
The objective of this research was to produce activated carbon from the cocoa almond shell. Samples were provided by Peruinka Industrias S.A. The preparation used the chemical activation method employing 60% concentration phosphoric acid. The variables were the carbonization temperature (200 °C, 250°, and 300 °C) and carbonization time (90, 120, and 150 minutes). To characterize the best product produced, the physicochemical properties of the activated carbon and the adsorption capacity using methylene blue dye were evaluated, these properties were assessed under the Peruvian Technical Standard 207.024. The optimal treatment found for the production of activated carbon with cocoa almond shell corresponds to a carbonization temperature and time of 300 °C and 150 minutes, respectively. The physicochemical characteristics of the obtained product were: Moisture 1.9413%, Density 0.5115 g/cm3, pH 3.19, Ash 25.4045%, Volatile Matter 67.1078%, and Fixed Carbon 7.4876.